Axial buckling resistance of partially encased columns - Abdelkadir, Fellouh (2016)
Partially Encased Columns (PEC) present good axial buckling resistance under fire, mainly due to the presence of concrete between flanges. The presence of concrete increases the mass and thermal inertia of the member and changes the variation of the temperature field within the cross section, in both the steel and concrete. The elastic buckling load of PEC under fire conditions may be calculated by the balanced summation method and by the finite element method. This work compares the results from both solution methods and provides the validation of the three dimensional model for different fire ratings of 30 and 60 minutes.